Volatile phytochemical composition of rhizome of ginger after extraction by headspace solid-phase microextraction, petroleum ether extraction and steam distillation extraction - Zhannan Yang, Weiping Yang, Quancai Peng, Qiansong He, Yong Feng, Shiqiong Luo, Zhengwen Yu (Bangladesh Pharmacological Society, 2009)
The sampling techniques headspace solid-phase microextraction (HS-SPME), petrol ether extraction (PEE) and steam distillation extraction (SDE) were compared for the GC-MS of volatile constituents present in ginger (Zingiber officinale). The effects of different parameters, such as extraction fibers, extraction time, extraction temperature and particle size ranges, on the HS-SPME of rhizome of ginger were investigated. Zingiberene (53.12%) were predominant components of ginger samples obtained by HS-SPME whereas those levels were 39.01% in the same samples by PEE and 35.05% in those by SDE, respectively. HS-SPME with polydimethylsiloxane (PDMS) fiber was more selective and particularly efficient for the isolation of volatile phytochemical composition and afforded a higher yield of total compounds than PEE and SDE. The specific compound isolated by SPME, which due to effective fiber, was much larger than that isolated by PEE or SDE. HS-SPME is a powerful tool for determining the volatile constitutes present in the traditional Chinese medicines.